Provision of Physics E-Comics to Improve Student Learning Outcomes on Straight-Motion Material at MTs Negeri 1 Kayong Utara - Nur Khanifatul Latifah; Tomo Djudin; Hamdani Hamdani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
The research was conducted to know the effectiveness of providing e-comics related to straight-motion material for improving student learning outcomes in class VIII MTsN 1 Kayong Utara. This type of research is experimental research that applies a non-equivalent control group design with an intact group random sampling technique. Based on the research data, the results were obtained, namely: 1) students who received e-comics and those who did not receive e-comics, their learning outcomes increased. The increase in learning outcomes in the experimental class was higher than that in the control class; 2) a significant difference was found in the learning outcomes of students who used e-comics and those who did not use e-comics with Sig. (2-tailed) < 0.05; 3) the provision of e-comics in learning is obtained with an effective level of 0.82 in the effective category. Therefore, e-comic media is effectively used in learning straight-motion material in class VIII MTsN 1 Kayong Utara.